El sistema de afloramiento Peruano. Un estudio numérico de las variabilidades espaciales y temporales - Huaringa, Enrique (2020)
One of the most important upwelling areas is o the Peruvian coast. Two regions are especially prominent: 11° to 12° S and 14° to 15° S. The upwelling is most intense in the northern area. In addition to the spatial change, there is a time variation with a pronounced annual period, with the maximum upwelling in the southern hemisphere winter. The Peruvian Current leaving the coast in this region may generate special conditions. A change in the whole system occurs when El Niño takes place. The Equatorial Front advances far to the south and coastal upwelling is suppressed. Compared to the large-scale aspects of the El Niño phenomenon itself, its impacts on the Peruvian upwelling system is much less well known. The work is to apply a numerical model and use the data generated by the observational program for calibration and validation purposes.